Lesions in different prefrontal sectors are associated with different types of acquired personality disturbances. (February 2022) - Barrash, Joseph; Bruss, Joel; Anderson, Steven W.; Kuceyeski, Amy; Manzel, Kenneth; Tranel, Daniel; Boes, Aaron D.
Abstract: "Frontal lobe syndrome" is a term often used to describe a diverse array of personality disturbances following frontal lobe damage. This study's guiding premise was that greater neuroanatomical specificity could be achieved by evaluating specific types of personality disturbances following acquired frontal lobe lesions. We hypothesized that three acquired personality disturbances would be associated with lesion involvement of distinct sectors of the prefrontal cortex (PFC): 1) emotional-social disturbance and ventromedial PFC, 2) hypoemotional disturbance and dorsomedial PFC, and 3) dysexecutive and dorsolateral PFC. In addition, we hypothesized that distressed personality disturbance would not be associated with focal PFC lesions in any sector. Each hypothesis was pre-registered and tested in 182 participants with adult-onset, chronic, focal brain lesions studied with an observational, cross-sectional design. Pre- and postmorbid personality was assessed by informant-rating with the Iowa Scales of Personality Change, completed by a spouse or family member. Two complementary analytic approaches were employed: 1) a hypothesis-driven region-of-interest (ROI) regression analysis examining the associations of lesions in specific PFC sectors with acquired personality disturbances; 2) a data-driven multivariate lesion-behavior mapping analysis, which was not limited to pre-specified regions. Each hypothesis received some support: (i) Emotional/social personality disturbance was most strongly associated with ventromedial PFC lesions in both statistical approaches. (ii) Hypoemotional disturbance was associated with dorsomedial PFC lesions in the ROI analyses, without any significant lesion-symptom mapping associations. (iii) Dysexecutive personality disturbance was associated with bilateral dorsolateral PFC lesions and ventromedial PFC lesions; lesion-symptom mapping showed maximal association of executive dysfunction with damage of the right middle frontal gyrus within the dorsolateral PFC. (iv) Distressed personality disturbance was not associated with lesions in any PFC sector. Altogether, the findings can be interpreted to indicate that damage to different prefrontal sectors may disrupt different anatomical-functional systems and result in distinct personality disturbances.